Vibrational Spectra and Normal Coordinate Calculations of para-Methoxy Benzoic Acid - Mohan, S.; Puviarasan, N.; Arul Dhas, D. (Asian Journal of Chemistry, 2010)
The laser Raman, infrared and FTIR spectra of p-methoybenzoic acid have been recorded in the regions 4000-30 cm-1 ,4000-600 cm-1 and 4000-200 cm-1 respectively in the solid phase.The observed frequencies of p-methoxy benzoic acid have beenassigned to various modes of vibrations in terms of fundamentals,overtones and combinations assuming Cs point group symmetry.The normal coordinate analysis has been carried out to check thevalidity of the assignments. The potential energy distributionassociated with normal modes was also reported here. The assignmentsof fundamental vibrations agree well with the calculatedfrequencies.